2010
DOI: 10.1002/pd.2508
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the need for extracorporeal membrane oxygenation and survival in congenital diaphragmatic hernia: a center's 10‐year experience

Abstract: The study confirms the LHR, GA at delivery and liver herniation as significant prenatal predictors of the need for ECMO or survival in cases with CDH. This information is helpful for counseling women with fetuses complicated by CDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
1
21
3
Order By: Relevance
“…A recent study by Jani et al [35] reported the O/E LHR be associated with BPD, defined as oxygen dependency at day 28, and the duration of ventilation. In contrast to our findings, need for ECMO therapy was not associated with the O/E LHR in a recent study [36] . However, in this study the authors pointed out that the indications for ECMO therapy varied widely in their study centers [36] .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A recent study by Jani et al [35] reported the O/E LHR be associated with BPD, defined as oxygen dependency at day 28, and the duration of ventilation. In contrast to our findings, need for ECMO therapy was not associated with the O/E LHR in a recent study [36] . However, in this study the authors pointed out that the indications for ECMO therapy varied widely in their study centers [36] .…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to our findings, need for ECMO therapy was not associated with the O/E LHR in a recent study [36] . However, in this study the authors pointed out that the indications for ECMO therapy varied widely in their study centers [36] . In our centers, ECMO criteria were well defined and did not change over time.…”
Section: Discussioncontrasting
confidence: 56%
“…Hutcheon et al [14] showed that neonatal and infant mortality significantly decreased with advancing gestation, from 25 and 36% at 37 weeks of gestation, respectively, to 17 and 20% at 40 weeks of gestation, respectively. Moreover, a study from Odibo et al [15] among 107 CDH cases found that gestational age at delivery was inversely correlated to the need for ECMO. However, Safavi et al [16] found no difference in mortality when dividing gestational age at delivery categorically as under 37 weeks, 37-38 weeks and 39 weeks or beyond.…”
Section: Resultsmentioning
confidence: 99%
“…The lung-to-head ratio (LHR), particularly LHR<1, 1018 and thoracic liver position (as compared to abdominal position) have been shown to be predictors of both death and need for ECMO use. 11,1416,18,19 More recently it has been demonstrated that increasingly abnormal stomach position is a strong predictor of not only death and ECMO, but also need for prolonged neonatal respiratory support. 20 This is likely due to the relationship of stomach position to liver position.…”
Section: Introductionmentioning
confidence: 99%